Mentorship Analysis in Improving the Quality of Internship Students at PT Asuransi Jasa Indonesia - Siti Nurul Fajri; Susan Febriantina; Eka Dewi Utari (Journal of Creative Power and Ambition (JCPA), 2026)
The increasing gap between academic competencies and labor market demands has encouraged higher education institutions to strengthen internship programs as a means of enhancing students’ work readiness. This study aims to analyze the implementation of mentorship, its contribution to improving the quality of internship students, and the supporting and inhibiting factors affecting mentorship effectiveness at PT Asuransi Jasa Indonesia (Jasindo). This research employed a qualitative case study approach conducted from September to December 2025. Data were collected through observation, interviews, and documentation involving internship students in the Retail Underwriting Unit and were analyzed using the Miles and Huberman interactive model with the assistance of NVivo 14. The findings reveal that mentorship was implemented through onboarding activities, task guidance, monitoring, work discussions, experience sharing, and performance evaluations involving both internal company mentors and external mentors from the National Research and Innovation Agency (BRIN). The mentorship program significantly improved students’ hard skills, soft skills, professional adaptability, and career readiness. Supporting factors included mentor support, direct project involvement, conducive work environments, communication, rewards, and field visits, while limited mentoring time, workload pressures, communication barriers, and scheduling uncertainties emerged as major challenges.